Dynamics of Arc Migration and Amalgamation Architectural Examples from the NW Pacific Margin - Itoh, Yasuto; Takano, Osamu; Takashima, Reishi; Nishi, Hiroshi; Yoshida, Takeyoshi (IntechOpen, 2017)
This book is devoted to the dynamics of arc migration and amalgamation on active plate margins, and we focus on the architectural examples from the NW Pacific margin. Multidisciplinary approach pursuing the complicated tectonic processes is based on stratigraphy, sedimentology, geochemistry, and geophysics. The first chapter is dedicated to the genetic analysis of sedimentary basins in and around arc-trench systems. The following block of chapters deals with the petrological, geochemical, and rock magnetic properties of arc constituents, which inform us of the migration history of crustal blocks on oceanic plates, and spatiotemporal fluctuation in modes of subduction and stress regimes upon the Eurasian convergent margins. Our vision is finally presented as a reconstruction model of plate motion around the study area since the Cretaceous (100 Ma). Diverse contents of this book surely provide the audience with the present accomplishments of tectonic researches for active margins by Earth scientists.